In vitro and in vivo antioxidant potential of the methanol extract, its fractions and isolated compounds of Piliostigma thonningi - Chioma Ifeoma Ibe; Eze Elijah Ajaegbu; Amara Anwuchaepe Ajaghaku; Peter Maduabuchi Eze; Ifeanyi Peter Onyeka; Christopher Obidike Ezugwu; Festus Basden Chiedu Okoye (Elsevier, 2022)
Background: In Africa, Piliostigma thonningii is utilized traditionally for the treatment of dysentery, diarrhea, and various stomach complications. Purpose: The study's aim is the screening of the extract/fractions of P. thonningii for antioxidant activities and isolation of some of the components. Methods: The root bark was extracted with methanol and subjected to further purification using liquid-liquid partitioning and chromatographic techniques. The isolated compounds were characterized by utilizing HPLC-DAD and 1D NMR spectroscopy. Results: The ethyl acetate fraction displayed best activity with total phenol content of 270 mgGAE/g, IC50 of 60.24 µg/ml (2,2-diphenyl-1-picrylhydrazyl (DPPH) assay) and EC50 of 653.4 µg/ml (ferric-reducing antioxidant power (FRAP) assay). For the in vivo antioxidant assay at 200 and 400 mg/kg, the ethyl acetate fraction produced significant (p < 0.05) inhibition of serum alanine aminotransferase (ALT), aspartate aminotransferase (AST) enzyme and lipid peroxidation activities just like 100 mg/kg silymarin, and also showed significant (p < 0.05) increase in serum antioxidant enzymes catalase (CAT) and superoxide dismutase (SOD). Five known compounds, which include 4-hydroxybenzoic acid, 3,4-dihydroxybenzoic acid, (2E)-3-(4‑hydroxy-3-methoxyphenyl)prop‑2-enoic acid, 8-(β-D-glucopyranosyl)-4',5,7-trihyroxyflavone and (3αR,9R,9αs)-7‑hydroxy-9(4‑hydroxy-3-methoxyphenyl)-6‑methoxy-3α,4,9,9α-tetrahydro-1H-benzo[f][2]benzofuran-3-one were detected from HPLC-DAD analysis of the active fractions. Compound 6 (anabellamide) and 7 (9-desoxy-α-conidendrin) were isolated and they showed lower inhibition of DPPH radical compared to the extract and ethyl acetate fraction from where they were isolated. Conclusion: This study revealed the potential of the P. thonningii root bark as a source of antioxidant molecules which can be applied in therapy.